A double fuzzy multi-criteria analysis to evaluate international high-performance aircrafts for defense purposes. (October 2022) - Sánchez-Lozano, J.M.; Correa-Rubio, J.C.; Fernández-Martínez, M.
Abstract: This paper contributes the first-known study involving international military high-performance aircrafts together with their weaponry systems for defense purposes. This technical study had the invaluable help from an advisory group of instructor pilots whose expertise in combat aircrafts allowed the calculation of the relative importance of qualitative criteria playing a key role in each analysis. The combination of a modified version of Analytic Hierarchy Process (AHP; to determine the weights of the criteria) and Technique for Order of Preference by Similarity to ideal Solution (TOPSIS; to assess each set of alternatives) approaches with fuzzy logic becomes especially appealing for this case of study. The best scores were obtained by the F-16 jet and the SCALP EG missile. First, the F-16 (with a defuzzified TOPSIS coefficient of 0.95) was closely followed by both jets Su-35 (2nd position, with a coefficient equal to 0.93) and Su-30 (third position, 0.89). However, the difference between the SCALP EG (1.02) and its chasing alternative, the Kh-59M (0.65), was significantly greater. Such results were reinforced by sensitivity analyses through a combination of fuzzy AHP-VIKOR. Highlights: Military high-performance aircrafts and their weaponry systems are evaluated. An advisory group of combat pilots determined the weights of the criteria. Fuzzy AHP and TOPSIS to assess alternatives based on sets of criteria. Linguistic labels and triangular fuzzy numbers to characterize qualitative criteria. The F-16 aircraft and SCALP EG missile were the best alternatives.